The Vitamin B1 and B12 Required by the Marine Dinoflagellate Lingulodinium polyedrum Can be Provided by its Associated Bacterial Community in Culture - Cruz-López, Ricardo; Maske, Helmut (Frontiers in Microbiology, 2016)
In this study we established the B1 and B12 vitamin requirement of the dinoflagellate Lingulodinium polyedrum and the vitamin supply by its associated bacterial community. In previous field studies the B1 and B12 demand of this species was suggested but not experimentally verified. When the axenic vitamin un-supplemented culture (B-ns) of L. polyedrum was inoculated with a coastal bacteria community, the dinoflagellate's vitamin growth limitation was overcome, reaching the same growth rates as the culture growing in vitamin B1B7B12-supplemented (B-s) medium. Measured B12 concentrations in the B-s and B-ns cultures were both higher than typical coastal concentrations and B12 in the B-s culture was higher than in the B-ns culture. In both B-s and B-ns cultures, the probability of dinoflagellate cells having bacteria attached to the cell surface was similar and in both cultures an average of six bacteria were attached to each dinoflagellate cell. In the B-ns culture the free bacterial community showed significantly higher cell abundance suggesting that unattached bacteria supplied the vitamins. The fluorescence in situ hybridization (FISH) protocol allowed the quantification and identification of three bacterial groups in the same samples of the free and attached epibiotic bacteria for both treatments. The relative composition of these groups was not significantly different and was dominated by Alphaproteobacteria (>89%). To complement the FISH counts, 16S rDNA sequencing targeting the V3-V4 regions was performed using Illumina-MiSeq technology. For both vitamin amendments, the dominant group found was Alphaproteobacteria similar to FISH, but the percentage of Alphaproteobacteria varied between 50 and 95%. Alphaproteobacteria were mainly represented by Marivita sp., a member of the Roseobacter clade, followed by the Gammaproteobacteria Marinobacter flavimaris. Our results show that L. polyedrum is a B1 and B12 auxotroph, and acquire both vitamins from the associated bacterial community in sufficient quantity to sustain the maximum growth rate.